PENGELOLAAN DANA TABARRU’ ASURANSI JIWA SYARIAH DALAM PEMBIAYAAN MURABAHAH DI BANK SUMSEL BABEL CABANG SYARIAH BATURAJA - Muhammad Iqbal (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
The existence of insurance in the modern era which is the embryo of conventional insurance based gharar, maysir, and usury ', making Islamic legal experts react by conducting research and analysis of the issue. The result proves that in Islamic law contains substance of insurance which can avoid the operational principle of gharar, maysir, and usury element '. This study aims to explain how the management of tabarru funds' sharia life insurance in murabahah financing in Bank Sumsel Babel Branch Sharia Baturaja. Insurance company that made the object of research is PT. Asuransi Bangun Askrida Unit Syariah. The research method used is descriptive qualitative method. The results concluded that the Management of Tabarru 'Sharia Life Insurance Fund PT. Asuransi Bangun Askrida Syariah Palembang Unit in Murabahah Financing at Bank Sumsel Babel Branch Sharia Baturaja uses insurance product mechanism with non saving element which separates the contribution fund into two parts, that is 42,5% for ujrah manager, and 57,5% for investment of tabarru fund '. If there is an underwriting surplus at the end of the period closing, it will be allocated 30% for Managers, 30% for tabarru 'funds reserves, and 40% for Participants who meet the requirements of obtaining surplus incentives. However, if there is an underwriting deficit in the management of the tabarru funds 'funds, the Insurance Company is obliged to cope with the shortage of tabarru' funds in the form of loans (qardh).